Promising galactose-decorated biodegradable poloxamer 188-PLGA diblock copolymer nanoparticles of resibufogenin for enhancing liver cancer therapy - Hao Dong; Li Tian; Meng Gao; Hong Xu; Chenghong Zhang; Li Lv; Jianbin Zhang; Changyuan Wang; Yan Tian; Xiaochi Ma (Taylor & Francis Group, 2017)
Liver cancer is one of the major diseases affecting human health. Modified drug delivery systems through the asialoglycoprotein receptor, which is highly expressed on the surface of hepatocytes, have become a research focus for the treatment of liver cancer. Resibufogenin (RBG) is a popular traditional Chinese medicine and natural anti-cancer drug that was isolated from Chansu, but its cardiotoxicity and hydrophobicity have limited its clinical applications. Galactosyl-succinyl-poloxamer 188 and galactosyl-succinyl-poloxamer 188-polylactide-co-glycolide (Gal-SP188-PLGA) were synthesized using galactose, P188, and PLGA to achieve active liver-targeting properties. RBG-loaded Gal-SP188-PLGA nanoparticles (RGPPNs) and coumarin-6-loaded Gal-SP188-PLGA nanoparticles (CGPPNs) were prepared. The in vitro cellular uptake, cytotoxicity, and apoptosis of nanoparticles in HepG2 cells were analyzed. The in vivo therapeutic effects of nanoparticles were assessed in a hepatocarcinogenic mouse model. The results showed that Gal-SP188-PLGA was successfully synthesized. The cellular uptake assay demonstrated that CGPPNs had superior active liver-targeting properties. The ratio of apoptotic cells was increased in the RGPPN group. In comparison to the other groups, RGPPNs showed superior in vivo therapeutic effects and anticancer efficacy. Thus, the active liver-targeting RGPPNs, which can enhance the pharmacological effects and decrease the toxicity of RBG, are expected to become a promising and effective treatment for liver cancer.